The coffee and mushrooms circles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Joint studies by the French research institute for development IRD (formerly ORSTOM) and the University of Mexico have identified mushrooms that can break down caffeine in coffee pulp. The pulp can then be used as animal feed, and as a growing base...